PENERAPAN WORDWALL SEBAGAI MEDIA GAME-BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA KELAS II: STUDI KASUS DI MIM 2 KOTA - Layli Ila Ramadhani; Siti Maria Ulfa; Juhairiyah; Evi Avia Lukmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the implementation of Wordwall as a game-based learning media in mathematics learning for grade II at MIM 2 Probolinggo City and its impact on student engagement and concept understanding. The research uses a descriptive qualitative approach with data collection techniques through interviews, classroom observations, and documentation.The results show that Wordwall is integrated in the core learning stage, especially in strengthening the concept of flat shapes through the matching games feature. The use of Wordwall is able to increase enthusiasm, focus, and active participation of students, as well as foster positive social interaction among students. Cognitively, Wordwall helps students understand mathematical concepts concretely through visual presentation, question variations, and instant feedback.The main obstacle in the application of this media includes limited devices and internet networks, which teachers overcome with classical learning strategies using projectors. The success of using Wordwall is highly dependent on the pedagogical role of the teacher in linking the media with learning objectives and flow.Overall, Wordwall is proven to be an effective innovative and interactive media that supports meaningful learning and improves the quality of student learning experiences in lower classes